IDENTIFIKASI KOMPETENSI YANG DIBUTUHKAN TENAGA AHLI TEKNIK BANGUNAN GEDUNG PADA INDUSTRI KONSTRUKSI - Agia Rezqiana; R. Eka Murtinugraha; Irika Widiasanti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Delays in construction projects often arise due to various factors, including inadequate planning, implementation, and supervision. Competent professionals play a crucial role in ensuring the success of all stages of building construction, from planning to execution and monitoring. Therefore, it is essential to involve skilled building engineering experts with the necessary competencies to oversee the entire project. This research aims to identify the required competencies for professionals in the field of building engineering. The literature review method was employed, involving an analysis of various literature sources addressing the same topic, including scholarly journal articles and relevant theses. The selection criteria for the literature review were articles published between 2020 and 2023, available in both English and Indonesian languages. A total of 25 articles were found to align with the research objective. Based on the content analysis of these articles, the most frequently mentioned competencies related to building engineering professionals are Building Information Modeling (BIM), advancements in building technology, effective communication, seismic-resistant building design, structural drawings/designs, structural element work methods, structural load and analysis, and the application of relevant standards in accordance with the nature of the work performed.